Effects of hypertriglyceridaemia on blood coagulation factor VII: a case control study of 110 cases - Aziz, Rehana; Alam, ASM Towhidul; Deb, Ajoy; Haque, Mahmudul (Journal of Chittagong Medical College Teachers' Association, 2011)
Keywords: Hypertriglyceridaemia; plasma coagulation factor VII; hypercoagulability; coronary artery disease DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9110 JCMCTA 2011; 22(1): 32-34